THE EDUCATION SYSTEM OF THE USA: PRESCHOOL EDUCATION, SECONDARY AND HIGHER EDUCATION, SCHOOL FORMS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the intricate layers of the  American educational system, encompassing preschool, secondary, and higher  education while also touching upon various school forms and educational models. It  provides a detailed overview of each educational level, emphasizing the foundational role of preschool education, the K-12 journey, and the diverse pathways available in  higher education.The article highlights the fundamental aspects of each educational  stage, discussing the objectives, subjects covered, and the transition from one level to the next. It also sheds light on the diverse array of educational institutions in the US,  including community colleges, four-year universities, specialized institutions, and both  public and private schools, elucidating their roles and characteristics